Relationship between Organizational Culture Openness and Teacher Readiness Quality with School Dynamic Effectiveness in One-Roof Schools - Nunuk Hariyati; Athalla Nauval Bhayangkara; Nia Islamiah; Wildan Hafizh Ahmadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Not many researchers or experts have studied how organizational culture, the quality of teacher readiness, and effective schools are dynamic, especially in one-roof schools in suburban areas whose geographical conditions are near the coast and mountains. This research aims to analyze the relationship between OCO and TRQ with SDE. This research is in 9 one-roof schools. This study is using the quantitative approach, non-experimental design. The respondent of this study consist of 87 respondents (teachers and principals). Data collection techniques by researchers were carried out using a questionnaire in the Google form through multiple choice. Descriptive analysis using IBM SPSS22 and inferential statistics using SmartPLS3. The result shows (1) the Javanese cultural factor of remote communities,